High‑energy emulsification of Allium sativum essential oil boosts insecticidal activity against Planococcus citri with no risk to honeybees - Modafferi, Antonino; Giunti; Urbaneja, Alberto; Laudani, Francesca; Latella; Pérez-Hedo, Mertixell; Ricupero, Michele; Palmeri, Vince; Campolo, Orlando (Springer, 2024)
The ecotoxicological consequences of synthetic pesticides have encouraged stakeholders to search for eco-friendly pest control tools, like essential oils (EOs). Nano-delivery systems (nanoparticles and nano-emulsions) seem ideal for developing EO-based biopesticides, although production processes should be standardized and implemented. In this study, nano-emulsions loaded with a high amount of Allium sativum L. EO (15%) were developed using different mixed bottom-up/top-down processes. Garlic EO was chemically analyzed by gas chromatography-mass spectrometry (GC-MS) and formulations were physically characterized using Dynamic Light Scattering (DLS) apparatus. The insecticidal activity against Planococcus citri Risso (Hemiptera: Pseudococcidae) and selectivity toward Apis mellifera L. (Hymenoptera: Apidae) worker bees was evaluated. Garlic EO was mainly composed of sulphur components (96.3%), with diallyl disulphide and diallyl trisulphide as the most abundant compounds (37.26% and 28.15%, respectively). Top-down processes could produce stable nano-emulsions with droplet size in the nanometric range (< 200nm) and good polydispersity index (PDI < 0.2). In contrast, the bottom-up emulsion was unstable, and its droplet size was around 500nm after 24 hours. High-energy emulsification processes significantly increased the residual toxicity of garlic EO against 3rd instar P. citri nymphs, whereas the developed formulations were harmless to A. mellifera workers in topical application. This study confirmed that the production process significantly affected the physical properties and efficacy against target pests. The lack of adverse impact on honeybees denotated the potential of these formulations as bioinsecticides in organic and/or IPM programs, although further extended ecotoxicological studies are necessary.